Inhibitory Effect and Mechanism of Water-Soluble Chitosan/Curdlan Edible Composite Coating on Botrytis cinerea in Cherry Tomato - YU Youwei, LIU Kunyu, ZHANG Shaoying, JING Ziyu, CHANG Jiaqi, LI Jiasi (Shipin Kexue)
In this study, the inhibitory effect of an edible composite composed of coating water-soluble chitosan and curdlan on postharvest infection of cherry tomatoes by Botrytis cinerea and the underlying mechanism was investigated. The mycelial growth, minimum inhibitory concentration (MIC), spore germination and membrane permeability of B. cinerea were studied. The results showed that the composite coating had a significant inhibitory effect on the growth of B. cinerea. After treatment with the composite coating, the cell membrane was damaged, resulting in leakage of intracellular contents and hyphal shrinkage. Meanwhile, it significantly inhibited the expansion of B. cinerea lesions. The composite coating might inhibit B. cinerea mainly by affecting the cell wall and membrane. These results suggest that the water-soluble chitosan/curdlan edible composite coating can be used as an effective antimicrobial material in the storage and preservation of cherry tomatoes.